Theoretical fundamentals of neoliberalism: some notes from Foucault, Dardot and Laval - Correia, Fabio Caires [UNESP]; Duarte, Fabio Henrtque; Perius, Oneide (Univ Federal Piaui, Editora, 2023)
The anti democratic turn produced by neoliberalism is, without a doubt, a sign of our times. But here we intend to show that studying it as a logical consequence of a new political rationality results in the painting of fa totala apocalyptic picture (1) for democracy, (2) for polities and (3) for the subject If we could continue to think of Neoliberalism as an ideology, whose field of forces would work with very well-defined mechanisms, but not as a dical transformation of the modes of political domination, it wohld be possible to understand the de democrazation that characterizes our time in the context in which is currently understood as thinkers macribed in the Marxist tradition, Le, as a new chapter in the historical tension between capitalism and democracy, In the present paper, we intend to reconstruct the notion of rationality, in Foucault, as it began to appear In Defense of Society and the way in which this notion is definitively associated with noqliberalism in The birth of biopolitics, with a vigw to specifying the way in which its novelty is articulated there In a second moment, we present the conflict between this new form of government and democratic politics. as Dardot and Laval's texts suggested Last but not least, we point out the epistemological limits that the Foucauldian perspective has to study the democratzation processes that pernieate contemporary capitalist societies from the concept of neoliberal rationality.
Keywords: Neoliberaliam; Sobjectivation; Biopolitics; World reason